IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING POETRY THROUGH CONTEXTUAL TEACHING AND LEARNING MODEL IN YEAR X IPA-2 OF MAN 2 WEST ACEH ACADEMIC YEAR 2022-2023 - Rosmininur, Rosmininur; Asmanidar, Asmanidar; Marsita, Marsita (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2022)
This study aimed to determine